ACHIEVING PRICE AND PERFORMANCE EQUALITY ON AND OFF THE GRID BY EXAMINING GLOBAL RENEWABLE ENERGY TRENDS - Aydın, Ömer; Demir, Zafer (Eskişehir Teknik Üniversitesi, 2021)
Renewable energy sources are an increasing trend in the world as an alternative solution to rapidly depleting fossil fuels. Due to the depletion of fossil fuel resources and the reduction of climate change, societies are forced to internalize these effects and to pave the way for sustainable energy technologies. Other reasons for preference are that these resources are cost-effective and environmentally friendly. Looking at rapidly falling cost curves such as solar and wind energy and the comparability of traditional production technologies in the global market help in establishing the price and performance balance. Today, with the storage options becoming more affordable, the popularity of renewable energy sources has increased. While storage methods provided an advantage for traditional energy sources in the past, today it has provided great convenience in terms of both distribution and transmission of electrical energy produced from renewable sources. The electrical energy obtained from renewable sources and the maturation of the technologies used to obtain this energy, the increase in distributed energy sources, the decrease in the costs of storage technologies, strong consumer behaviors affect the price-performance balance, as well as the way we produce, use and trade electricity. In this study, global renewable energy trends will be examined and information will be given on price and performance equality on and off the grid.

Yenilenebilir enerji kaynakları, hızla tükenmekte olan fosil yakıtlara alternatif bir çözüm olarak dünyada giderek artan bir eğilimdir. Fosil yakıt kaynaklarının tükenmesi ve iklim değişikliğinin etkilerinin artması nedeniyle toplumlar bu etkileri içselleştirmek ve sürdürülebilir enerji teknolojilerinin önünü açmak zorunda kalmaktadır. Diğer tercih nedenleri ise bu kaynakların maliyet etkin ve çevre dostu olmasıdır. Güneş ve rüzgar enerjisi gibi hızla düşen maliyet eğrilerine bakmak ve küresel pazarda geleneksel üretim teknolojilerinin karşılaştırılabilirliği, fiyat ve performans dengesinin kurulmasına yardımcı olur. Günümüzde depolama seçeneklerinin daha ekonomik hale gelmesiyle yenilenebilir enerji kaynaklarının popülaritesi artmıştır. Depolama yöntemleri geçmişte geleneksel enerji kaynakları için avantaj sağlarken, günümüzde yenilenebilir kaynaklardan üretilen elektrik enerjisinin hem dağıtımı hem de iletimi açısından büyük kolaylıklar sağlamıştır. Yenilenebilir kaynaklardan elde edilen elektrik enerjisi ve bu enerjiyi elde etmek için kullanılan teknolojilerin olgunlaşması, dağıtık enerji kaynaklarının artması, depolama teknolojilerinin maliyetlerinin düşmesi, güçlü tüketici davranışları fiyat-performans dengesini etkilediği gibi kullanım şekline de etki etmektedir. Bu çalışmada küresel yenilenebilir enerji trendleri incelenecek ve şebekede ve şebeke dışında fiyat ve performans eşitliği hakkında bilgi verilecektir.
KÜRESEL YENİLENEBİLİR ENERJİ TRENDLERİ İNCELENEREK ŞEBEKEYE BAĞLI VE BAĞIMSIZ FİYAT VE PERFORMANS EŞİTLİĞİNİN ELDE EDİLMESİ
Keywords: Engineering; Mühendislik